His last bow, with ebook eaudiobook - Doyle, Sir Arthur Conan (Tantor Media, 2009)
Created by Scottish author and physician Sir Arthur Conan Doyle in 1887, Sherlock Holmes was a brilliant London-based consulting detective, famous for his intellectual prowess and powers of deductive reasoning. His Last Bow is the fourth of Doyle's Sherlock Holmes short story collections and features eight mysterious tales: "The Adventure of Wisteria Lodge," "The Adventure of the Cardboard Box," "The Adventure of the Red Circle," "The Adventure of the Bruce-Partington Plans," "The Adventure of the Dying Detective," "The Disappearance of Lady Francis Carfax," "The Adventure of the Devil's Foot," and the title story, "His Last Bow." It is in this last story that Holmes emerges from a retirement of beekeeping to stop the spy Baron Von Bork from disclosing secret English documents at the approach of World War I.